Investigation Including VIIIR: AG Multimeric Analysis of a Large Kindred with Type IIA von Willebrand’s Disease Showing a Dominant Inheritance and Similar Gene Expression in Four Generations - Hill, F G H; Enayat, M S; George, A J (Thrombosis and Haemostasis, 1983)
Forty-two members of a family have been studied with bleeding times, platelet aggregation, platelet retention in glass beads, measurement of factor VIII associated activity, 2-dimensional electrophoresis and multimeric analysis of factor VIII related antigen (VIIIR:AG). Eleven individuals with type IIA disease and one with asymptomatic and another with symptomatic type I disease have been studied. The degree of absence of high and intermediate multimers and the abnormal triplet configuration in the two remaining multimers was consistent in all affected family members. Multimeric analysis provides a unique and precise way of studying qualitative defects of VIIIR:AG and thereby the evaluation of gene expression in family studies.
Keywords: von Willebrand’s disease; Type IIA variants; Multimeric analysis; Genetics of von Willebrand’s disease